2020
DOI: 10.3390/genes11101201
|View full text |Cite
|
Sign up to set email alerts
|

Two New Cases of Hypertrophic Cardiomyopathy and Skeletal Muscle Features Associated with ALPK3 Homozygous and Compound Heterozygous Variants

Abstract: Hypertrophic cardiomyopathy associated with damaging variants in the ALPK3 gene is a fairly recent discovery, and only a small number of patients have been described thus far. Here we present two additional patients with hypertrophic cardiomyopathy caused by biallelic variants in ALPK3. Genetic investigation was performed using a targeted gene panel consisting of known cardiomyopathy-associated genes and whole exome sequencing. The patients showed a large difference in the age of onset, and both presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…There were only 2 of 10 heterozygous family members in previously described cases that showed hypertrophy and with an atypical distribution of hypertrophy [ 33 ]. Additionally, in a recent study [ 42 ], the first case of symptomatic ALPK3 -associated cardiomyopathy presenting in adulthood is reported, leading to cardiac transplantation 10 years after the presentation of symptoms. This patient, though, carried a homozygous nonsynonymous single-nucleotide variant in exon 10 of ALPK3, underscoring the variability of symptoms and onset of disease that is seen in cases of cardiomyopathy caused by biallelic variants in ALPK3.…”
Section: Discussionmentioning
confidence: 99%
“…There were only 2 of 10 heterozygous family members in previously described cases that showed hypertrophy and with an atypical distribution of hypertrophy [ 33 ]. Additionally, in a recent study [ 42 ], the first case of symptomatic ALPK3 -associated cardiomyopathy presenting in adulthood is reported, leading to cardiac transplantation 10 years after the presentation of symptoms. This patient, though, carried a homozygous nonsynonymous single-nucleotide variant in exon 10 of ALPK3, underscoring the variability of symptoms and onset of disease that is seen in cases of cardiomyopathy caused by biallelic variants in ALPK3.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus genes and advancement. KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Exome libraries were enriched and sequenced on the Illumina HiSeq 2000 Genome Analyzer (Illumina, San Diego, CA, USA), using a HiSeq Sequencing Kit (Illumina) according to the manufacturer’s instructions. Bioinformatic analyses were made as described previously [ 34 , 35 , 36 , 37 ]. Based on the possible inheritance models of AF in the pedigree ( Figure 1 A), the variants that did not match any reasonable inheritance pattern of AF were filtered out.…”
Section: Methodsmentioning
confidence: 99%